Empowering PGMI Students to Develop AI-Integrated Teaching Materials: Building Ethical and Innovative Future Leaders - Berlian, Raisa; Wahyuni, Yulia Septi; Rahmi, Yesika Novita (IDRIS Darulfunun Institute, 2025)
The rapid advancement of Artificial Intelligence (AI) has brought significant transformation to the field of education, including Islamic elementary teacher education (PGMI). This study aims to explore how PGMI students can be empowered to develop AI-integrated teaching materials that promote innovation, ethical awareness, and leadership readiness for the future. This research employed a qualitative descriptive method involving PGMI students at Universitas Muhammadiyah Riau as the participants. Data were collected through observation, interviews, and documentation of the process of designing, implementing, and evaluating AI-assisted learning media, and analyzed through data reduction, data display, and conclusion drawing. The results reveal that students are able to integrate AI creatively and ethically in developing teaching materials. The use of AI enhances students’ technological competence, critical thinking, and creativity while fostering ethical responsibility in technology utilization. Thus, integrating AI into learning media development serves as a strategic effort to prepare PGMI students as innovative and ethical future educators and leaders in Islamic education.